2011
DOI: 10.1093/ntr/ntr041
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Hookah Use among High School Students

Abstract: Hookah use is becoming a commonly acceptable behavior among adolescents, and risk perception is a significant factor. Presence of hookah lounges are associated with increased hookah use among high school students and should be a target of further regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
101
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(113 citation statements)
references
References 30 publications
7
101
1
4
Order By: Relevance
“…El papel de los amigos también ha estado presente en la iniciación al consumo de tabaco en pipa de agua en nuestro trabajo, puesto que el 83.1% de los alumnos se ha incorporado a la primera sesión por medio de un amigo, dato similar a los hallados en otros estudios (Braun, Glassman, Wohlwend, Whewell y Reindl, 2012;Smith et al 2011b). …”
Section: Análisis De Datosunclassified
See 1 more Smart Citation
“…El papel de los amigos también ha estado presente en la iniciación al consumo de tabaco en pipa de agua en nuestro trabajo, puesto que el 83.1% de los alumnos se ha incorporado a la primera sesión por medio de un amigo, dato similar a los hallados en otros estudios (Braun, Glassman, Wohlwend, Whewell y Reindl, 2012;Smith et al 2011b). …”
Section: Análisis De Datosunclassified
“…En lo referente al uso compartido de la boquilla se aprecia, en base a los trabajos consultados y a los resultados de nuestro estudio que dicha conducta parece ser una práctica habitual entre los fumadores de pipa de agua. Así, más de la mitad de nuestros estudiantes (59.8%) comparte la boquilla la mayoría de las veces, y casi siempre con los amigos (94.6%), siendo estos porcentajes, respectivamente, muy próximos al 61.7% aportado por Smith et al (2011b), y al 94% observado en el estudio de Asfar et al (2005). Este hecho podría ser explicado a través de argumentos recogidos en otros estudios, en donde los jóvenes consideran que compartir la boquilla es similar a invitar a alguien a beber del mismo vaso o botella (Statens folkhälsoinstitut, 2010).…”
Section: Análisis De Datosunclassified
“…We included in our models individual and institutional characteristics that existing research suggests may have an association to waterpipe tobacco smoking ( Supplementary Table 1 ; Martinasek et al, 2011 ;Smith et al, 2011 ). Because the variables age and year in school were highly correlated, model instability resulted when we included both of these variables in multivariable models.…”
Section: Analysesmentioning
confidence: 99%
“…Second, it may increase actual access to the product. For example, adolescents who know of a hookah (tobacco waterpipe) lounge in their community are more likely to have used hookah (Smith et al, 2011), and those with greater density of tobacco retailers near their home have greater intentions to smoke, and thereby greater likelihood of future smoking (Mennis et al, 2016). Third, presence of a specialty retailer near a school may increase students' exposure to promotional materials (e.g., product advertisements), which previous studies have found is correlated with higher odds of vaping (Agaku and AyoYusuf, 2014;Singh et al, 2016a), and causally linked with tobacco use (DiFranza et al, 2006), including smoking initiation (Henriksen et al, 2010), and with higher odds of adolescent alcohol consumption (Hurtz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%